From a Yankee to a Rebel Diary The collective Civil War Diaries of Private George Washington Hall 14th Georgia Infantry and Private Jacob Elsesser 9th Pennsylvania Reserves - Hall, Mary T. (Lot's Wife Publishing Staunton, VA, 2025)
Diary entries from soldiers on both sides of the Civil War including their activities after the war.
Donated by the author, Mary T. Hall, Military History Professor at St. Mary's College of Maryland